Enhancement of the Seebeck coefficient in ferrofluid based thermoelectric materials: A numerical study. (2021) - Vasilakaki, M.; Chikina, J.; Shikin, V.B.; Ntallis, N.; Peddis, D.; Varlamov, A.A.; Trohidou, K.N.
Abstract: It has been demonstrated that the thermocells, which contain ionically stabilized magnetic nanoparticles (ferrofluids) dispersed in aqueous electrolytes, show enhanced Seebeck coefficient. We have addressed this issue by deriving an analytic expression that relates the Seebeck coefficient to the chemical potential and its temperature derivative taking into account the nanoparticle's intrinsic characteristics, i.e. magnetization and magnetic anisotropy. Mesoscopic scale modelling with the implementation of the Monte Carlo Metropolis algorithm has been performed on diluted assemblies of γ-Fe2 O3 and CoFe2 O4 nanoparticles – commonly used ferrofluid materials with different magnetic anisotropies and particle concentrations - to calculate the particle Seebeck coefficient at different temperatures. Importantly, our numerical results show enhancement of the Seebeck coefficient with the increase of the magnetic particle anisotropy and particle concentrations with a maximum that shifts to higher temperatures as the anisotropy increases. Our findings suggest that by tailoring the magnetic particle anisotropy, enhanced thermoelectric signal can be achieved in ferrofluid based thermoelectric materials.